On Remittances, Foreign Currency Exposure and Credit Constraints: Evidence from Nepal - Nephil Matangi Maskay; Sven Steinkamp; Frank Westermann (Center for Economic Studies and ifo Institute (CESifo), 2014)
In this paper, we investigate whether foreign currency accounts help overcome credit constraints in developing countries. We analyze a novel bank-level data set from Nepal, where a steady inflow of remittances has contributed to foreign currency deposits on commercial bank balance sheets. In this data set we find that: (i) Banks hedge their FX exposure by investing in FX assets. (ii) Banks also hedge indirectly via their sectoral lending composition: Banks with a large share of FX deposits primarily lend to firms in traded-goods sectors. They lend only little to the non-traded sectors, as well as deprived sectors of the economy that have been targeted by various support programs. While the direct impact of FX accounts on relaxing credit constraints thus appears small, and biased towards specific sectors, there is also a substantial indirect effect via the additional creation of domestic deposits - that benefits all sectors of the economy.
Keywords: F31; F24; E58; 330; foreign currency deposits; sectoral lending; financial development